Improving the language classroom with Facebook on mobile phones - Gabarre, Serge; Gabarre, Cécile; Din, Rosseni; Mei, Fung Yong (2013)
This paper relates an action research conducted in a French language course where Facebook on mobile phones were used instead of the university’s dedicated learning management system (LMS). The problems encountered when using the LMS were manifold: students were not able to initiate forum discussions, post multimedia documents and generally lacked the motivation to use the target language in the online environment. A study of the literature revealed that similar problems were resolved through the incorporation of social networking sites in the classroom. Furthermore, past studies have highlighted the pedagogical advantages of mobile learning with anywhere and anytime learning. Therefore, it was anticipated that combining Facebook with mobile phones could provide a solution through the affordances provided by both technologies. A two-cycle action research was conducted over the course of one semester with one cohort of students. Every student was provided with a smartphone and a permanent access to mobile Internet. All activities which were previously conducted on the LMS were transferred to Facebook. At the end of each cycle, semi-guided individual interviews were conducted with ten students to evaluate the new pedagogical setup. Data was subsequently coded and analysed with the ATLAS.ti software. Findings revealed the positive impact of using Facebook and mobile phones to promote motivation and participation. Although this research advocates using alternatives to the more classic LMS, several issues such as lack of privacy and cyber-quarrels were encountered. This paper offers solutions to facilitate the transition to a novel form of LMS empowering the students.